Development and experiment of rice hill-drop drilling machine for dry land based on proportional speed regulation - Wei, Fu; Zhiyuan, Zhang; Ying, Zang; Xiwen, Luo; Shan, Zeng; Zaiman, Wang (International Journal of Agricultural and Biological Engineering, 2017)
Rice precision hill-drop drilling technique in dry land uses fixed hill spacing to achieve orderly planting of crops and to attain good ventilating and day-lighting effects in rice fields. The technique is also beneficial in improving root growth and root structure and in increasing lodging resistance. The high-yield record of Xinjiang Production and Construction Corp’s first division for three consecutive years shows that rice precision hill-drop drilling technique in dry land is one of the important directions to developed rice cultivating mechanization technology. To further improve the quality of rice precision hill-drop drilling machine for dry land, a single profiling, electro-hydraulic proportional real-time adjustment of system was developed according to the agronomic requirements. This machine can simultaneously finish various kinds of seedbed leveling, furrowing and seeding operations, as well as soil covering and pressing. Electro-hydraulic proportional speed regulation makes an AMESim simulation test and analyzes the stability and error of hydraulic adjusting planting distance. Bench testing was carried out on the metering device by simultaneously employing high speed photography technology and analyzing the relationship of the high speed of hill distance and seed charge height. Finally, machine trial was completed. The two-year field experiments of Xinjiang Production and Construction Corp showed that when the machine operation speed is 2.8-3.2 km/h, the sowing depth percent of pass is 75% or higher, the qualified rate of row spacing is 80% or more, the pass rate of row spacing is 90% or higher, and the quantity per hill is 75% or higher. This machine met the various indicators of hill sowing quality requirements. Keywords: rice, hill-drop drilling for dry land, quality of precision sowing, proportional speed regulation, field experiment DOI: 10.25165/j.ijabe.20171004.3125 Citation: Fu W, Zhang Z Y, Zang Y, Luo X W, Zeng S, Wang Z M. Development and experiment of rice hill-drop drilling machine for dry land based on proportional speed regulation. Int J Agric & Biol Eng, 2017; 10(4): 77–86.